A Cytotoxic Flavanone from The Pod Peels of Theprosia vogelii Hook.f. - Valentina Adimurti Kusumaningtyas; Nia Sri Hardianti; Melina Melina; Lia Dewi Juliawaty; Yana Maolana Syah (Syarif Hidayatullah State Islamic University, 2020)
Tephrosia vogelii Hook.f. is a species of the family Fabaceae (Leguminoceae). These plants are termed ″Polong-polongan″ in Indonesia, and are known to contain active flavonoid groups. Previous studies have shown the isolation of one known flavanone: isolonchocarpin from methanol extract, and the structure obtained was established based on chemical evidence as well as spectroscopic methods, including NMR, and also by a comparison with published data. This research is aimed at evaluating the cytotoxic property of methanol extract against larvae of Arthemia salina Leach, using the Brine Shrimp Lethality Test (BSLT) method. The results show potent cytotoxicity at LC50 of 41.40 ppm.